A new structure of 12Slot-10Pole field-excitation flux switching synchronous machine for hybrid electric vehicles - Yahaya, Intan Fazlina (2014)
The new structure 12Slot-10Pole-field excitation flux switching synchronous machine (FEFSSM) with all active parts of the field excitation coil (FEC) and the armature coil is located in the stator, used for hybrid electric vehicles (HEVs). Design of the new structure different from the previous design which no permanent magnets. For a high-speed motor applications together with the system coupled with reduction gear, designed the rotor consists of a single piece of iron make it even stronger. The target of the same design specification motor in IPMSM used for LEXUS RX400h with a maximum torque of 210Nm with a 4:1 gear reduction ratio, 123kW maximum power, maximum power density of more than 3.5kW/kg, and a maximum speed of 20,000 r / min. To optimize the design, the design parameters of the rotor, the armature and the FEC changed repeatedly until the target is achieved with a maximum density 30A/mm2 for both the armature and the FEC. The end result after optimizing the design allows the latest designs with the same power density in the IPMSM can be used in commercial SUVHEV.